Implementation of Multi-GPU Based Lattice Boltzmann Method for Flow Through Porous Media (Advances in Applied Mathematics and Mechanics, 2018)
The lattice Boltzmann method (LBM) can gain a great amount ofperformance benefit by taking advantage of graphics processing unit(GPU) computing, and thus, the GPU, or multi-GPU based LBM can beconsidered as a promising and competent candidate in the study oflarge-scale fluid flows. However, the multi-GPU based latticeBoltzmann algorithm has not been studied extensively, especially forsimulations of flow in complex geometries. In this paper, throughcoupling with the message passing interface (MPI) technique, wepresent an implementation of multi-GPU based LBM for fluid flowthrough porous media as well as some optimization strategies basedon the data structure and layout, which can apparently reduce memoryaccess and completely hide the communication time consumption. Thenthe performance of the algorithm is tested on a one-node clusterequipped with four Tesla C1060 GPU cards where up to 1732 MFLUPS isachieved for the Poiseuille flow and a nearly linear speedup withthe number of GPUs is also observed.